Long‐term complications of glycogen storage disease type Ia in the canine model treated with gene replacement therapy. Issue 6 (24th July 2018) - Brooks, Elizabeth D.; Landau, Dustin J.; Everitt, Jeffrey I.; Brown, Talmage T.; Grady, Kylie M.; Waskowicz, Lauren; Bass, Cameron R.; D'Angelo, John; Asfaw, Yohannes G.; Williams, Kyha; Kishnani, Priya S.; Koeberl, Dwight D.
Abstract: Background: Glycogen storage disease type Ia (GSD Ia) in dogs closely resembles human GSD Ia. Untreated patients with GSD Ia develop complications associated with glucose‐6‐phosphatase (G6Pase) deficiency. Survival of human patients on intensive nutritional management has improved; however, long‐term complications persist including renal failure, nephrolithiasis, hepatocellular adenomas (HCA), and a high risk for hepatocellular carcinoma (HCC). Affected dogs fail to thrive with dietary therapy alone. Treatment with gene replacement therapy using adeno‐associated viral vectors (AAV) expressing G6Pase has greatly prolonged life and prevented hypoglycemia in affected dogs. However, long‐term complications have not been described to date. Methods: Five GSD Ia‐affected dogs treated with AAV‐G6Pase were evaluated. Dogs were euthanized due to reaching humane endpoints related to liver and/or kidney involvement, at 4 to 8 years of life. Necropsies were performed and tissues were analyzed. Results: Four dogs had liver tumors consistent with HCA and HCC. Three dogs developed renal failure, but all dogs exhibited progressive kidney disease histologically. Urolithiasis was detected in two dogs; uroliths were composed of calcium oxalate and calcium phosphate. One affected and one carrier dog had polycystic ovarian disease. Bone mineral density was not significantly affected. Conclusions: Here, we show that the canine GSD Ia model demonstrates similar long‐term complications as GSD Ia patients in spite of gene replacement therapy. Further development of gene therapy is needed to develop a more effective treatment to prevent long‐term complications of GSD Ia.